A Study of Elders’ Health Status and Perception about Old Age - Timalsina, Keshab Prasad (International Research Journal of MMC, 2021)
The health status of elders and elders’ perception regarding old age in a community is an important issue in a society. The present study aims to assess the health status and perception of old age of elderly population of Nijgadh Municipality. A descriptive cross-sectional study has been carried out among 204 elders taken from the community through simple random sampling method. The data were collected through face to face structured interview schedule in 2021. The descriptive and inferential statistical analysis of the collected data showed that the about 20 percent elders had got good status of health but remaining (about 80%) of them were suffering from some kinds of health complications. Similarly, more than 73 percent of elders felt their life more problematic. This study measured significant variation (p<0.05) of level of health status with only three socio-demographic variables (age, caste, and feeling of helplessness among the variables (gender, age groups, caste, living with or without spouse, literacy status, and feeling helplessness. Furthermore, this study measured significant variation (p<0.05) of perception about old age of elderly population with only three socio-demographic variable (age, caste, and feeling of helpless) among the variables (gender, age groups, caste, living with or without spouse, literacy status, and feeling helplessness). Based on the study, it can be said that age, caste, and feeling of helplessness status of elderly population were the major factors for creating variations in health status and perceptions of elderly life. The policies, programs, and community effort are needed for managing regular health service practice. Similarly, all the community members must be serious for keeping elders happy by managing their requirement with love which may require collective action from social, health and justice sectors.